Optimising Legume Integration, Nitrogen Fertilisation, and Irrigation in Semi-Arid Forage Systems - Luís Silva; Sofia Barbosa; Fernando Cebola Lidón; Benvindo Maçãs; Salvatore Faugno; Maura Sannino; João Serrano; Paola D’Antonio; Costanza Fiorentino; Francesco Cellini; Paulo Ferreira; Luís Alcino Conceição (Nitrogen, 2025)
Monoculture systems depend on high nitrogen (N) fertilisation. Incorporating legumes into forage crops offers a sustainable alternative with agronomic and economic benefits. This study assesses the impact of legumes in fodder systems, evaluating yield, N use efficiency (NUE), and profitability while identifying the best cropping strategy under semi-arid conditions. The experiment, conducted at Herdade da Comenda, Elvas, Portugal, used a split–split-plot randomised block design to analyse N doses, forage species, and irrigation. Economic metrics, including costs, net revenue, return on investment, and risk analysis, were also assessed. Moderate N doses (120 kg ha−1) resulted in significantly higher NUE (15.67 kg kg−1 N) than higher doses (200 kg ha−1), which yield only 1.40 kg kg−1 N (p < 0.05), particularly in mixed fodder crops. Irrigation improved N absorption, crop nutrition, and yield, leading to higher profitability despite increased initial costs. Agronomically, irrigation and N doses influenced yield and nutrient uptake, while no significant differences were observed between different forage crops in terms of yield or NUE. Economically, the irrigated mixed crop showed the highest return on investment (ROI = 247.37 EUR ha−1), whereas ryegrass presented lower financial risk (BE = 2213.24 kg ha−1) due to lower establishment costs. Yield was the strongest predictor of net profit (R2 = 0.89). Looking ahead, optimising N management, irrigation strategies, and mixed grass–legume crops will be crucial to maximising economic returns while minimising environmental impacts.